Telomere dysfunction and chromothripsis. Issue 12 (29th February 2016) - Ernst, Aurélie; Jones, David T.W.; Maass, Kendra K.; Rode, Agata; Deeg, Katharina I.; Jebaraj, Billy Michael Chelliah; Korshunov, Andrey; Hovestadt, Volker; Tainsky, Michael A.; Pajtler, Kristian W.; Bender, Sebastian; Brabetz, Sebastian; et al.
Abstract : Chromothripsis is a recently discovered form of genomic instability, characterized by tens to hundreds of clustered DNA rearrangements resulting from a single dramatic event. Telomere dysfunction has been suggested to play a role in the initiation of this phenomenon, which occurs in a large number of tumor entities. Here, we show that telomere attrition can indeed lead to catastrophic genomic events, and that telomere patterns differ between cells analyzed before and after such genomic catastrophes. Telomere length and telomere stabilization mechanisms diverge between samples with and without chromothripsis in a given tumor subtype. Longitudinal analyses of the evolution of chromothriptic patterns identify either stable patterns between matched primary and relapsed tumors, or loss of the chromothriptic clone in the relapsed specimen. The absence of additional chromothriptic events occurring between the initial tumor and the relapsed tumor sample points to telomere stabilization after the initial chromothriptic event which prevents further shattering of the genome. Abstract : What's new? Chromothripsis is characterized by extensive locally clustered genomic rearrangements, whereby chromosome shattering is followed by rejoining of the DNA fragments by error‐prone repair mechanisms. The present study elaborates on a previously proposed role in the initiation of chromothripsis for telomere erosion and breakage‐fusion‐bridge (BFB) cycles, in which chromosomes repeatedly break and are rejoined. In cells lacking normal mechanisms for genome preservation, telomere attrition and BFB cycles induced chromothripsis. Subsequent activation of tumor‐specific telomere maintenance mechanisms prevented further chromosomal shattering. The findings suggest that telomere maintenance pathways may represent therapeutic targets in chromothripsis‐positive tumors.